Ocularcentric Labour: “you don’t do this for money” - Sappey, Jennifer; Maconachie, Glenda (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2012)
This article is a response to Lansbury’s call (2009) in this journal for a re-conceptualization of work and employment. It supports Lansbury’s belief that the employment relationship cannot be understood in isolation from wider social change. Building on the tradition of emotional labour and aesthetic labour, this study introduces theoretically and empirically the concept of “ocularcentric labour” (the worker seeking the adoring gaze of the client as the primary employment reward). This paper seeks to establish: the empirical generalizability of ocularcentric labour; its conceptual differentiation with aesthetic and emotional labour; and the implications of ocularcentric labour for industrial relations and collective interest representation.Through a study of the employment relationship in the commercial health and fitness industry in Queensland (Australia), we identify this new type of labour as one in which the worker’s primary goal is to seek the psycho-social rewards gained from exposing their own body image. This quest shapes the employment relationship (both the organization of work and the conditions of employment). We argue that for many fitness workers the goal is to gain access to the positional economy of the fitness centre to promote their celebrity. For this they are willing to trade-off standard conditions of employment and direct earnings, and exchange traditional employment rewards for the more intrinsic psycho-social rewards gained through the exposure of their physical capital to the adoration of their gazing clients. As one worker said “You don’t do this for money.” Significantly, with ocularcentric labour the worker becomes both the site of production and consumption.The study draws on quantitative and qualitative data captured from the Australian health and fitness industry with one snapshot taken in 1993 and another in 2008. The conclusion draws together the key conceptual and empirical points and findings and examines the implications for the conceptualization of IR in the contemporary economy.